Analysis of changes in water quality and treatment effectiveness of seven major river basins in China from 2001 to 2020 - Yang, Qin; Chen, Jingsheng; Liu, Yuyi; Li, Yangguang; Zhang, Haigang; Zhang, Jing; Sun, Xiao; Lu, Mingyang; Ma, Rongqian; Wu, Yanlin (Frontiers in Environmental Science, 2024)
The seven major river basins (the Yangtze River, the Yellow River, the Pearl River, the Songhua River, the Huai River, the Hai River and the Liao River) are the most important surface water resources in China, but there is a lack of quantitative analyses of water quality change trends, horizontal comparisons of governance effects, and systematic review of effective policies since the 21st century. Based on the water resources bulletin and environmental status bulletin issued by government departments, the changes in water quality, pollutant indicators and treatment effectiveness of seven major basins from 2001 to 2020 have been scientifically analyzed using mathematical and statistical methods. (1) Over the period 2001 to 2020, the overall water quality in the seven major river basins exhibited a gradual improvement. Different basins demonstrated varied growth values for Grade I-III water, reduction values for Grade IV-V, and inferior Grade V water. (2) Between 2001 and 2020, changes in sewage discharge volume and types led to adjustments in the main pollutant indicators of the seven basins. (3) The ranking of the pollution degree in the seven major basins exhibited dynamic changes but also remained relatively stable during specific periods or years. (4) Assessing the average annual growth rate of Grade I-III water and the average annual reduction rate of Grade IV-V and inferior Grade V water, the Huai River basin demonstrated the most outstanding governance effectiveness, while the Liao River basin, the Yellow River basin, and the Songhua River basin also achieved notable treatment results. (5) The improvement in water quality across the seven major river basins can be attributed to scientific planning, enhanced policies and regulations, surge in investment in water conservancy infrastructure, heightened environmental protection awareness, application of green production technology. To sum up, the research findings not only provide a scientific foundation for the governance and protection of the seven major basins but also offer a valuable reference for other developing countries to strike a balance between economic development and environmental protection.